Respuesta :

Answer:

[tex]B=\sqrt{2}[/tex]

Step-by-step explanation:

Original equation:

[tex]B = \sqrt{2+\sqrt{3}} - \sqrt{2 - \sqrt{3}}\\[/tex]

Square both sides:

[tex]B^2=(\sqrt{2+\sqrt{3}})^2 + 2(\sqrt{2+\sqrt{3}} * (-\sqrt{2 - \sqrt{3}}) + (-\sqrt{2-\sqrt{3}})^2[/tex]

Cancel out the square roots and squares:

[tex]B^2=2+\sqrt{3}}+ 2(\sqrt{2+\sqrt{3}} * (-\sqrt{2 - \sqrt{3}}) + 2-\sqrt{3}[/tex]

Add the sqrt(3) and -sqrt(3) as well as 2 and 2

[tex]B^2=4 + 2(\sqrt{2+\sqrt{3}} * (-\sqrt{2 - \sqrt{3}})[/tex]

Use the identity: [tex]\sqrt{a} * \sqrt{b} = \sqrt{a * b}[/tex] to rewrite the two square roots being multiplied:

[tex]B^2=4 + 2(-\sqrt{(2+\sqrt{3}) * (2 - \sqrt{3}}))[/tex]

Use difference of squares: [tex](a-b)(a+b) = a^2-b^2[/tex]

[tex]B^2=4 + 2(-\sqrt{2^2-\sqrt{3}^2})[/tex]

Square both sides

[tex]B^2=4 + 2(-\sqrt{4-3})[/tex]

Subtract:

[tex]B^2=4 + 2(-\sqrt{1})[/tex]

Evaluate square root of 1:

[tex]B^2=4 + 2(-1)[/tex]

Multiply

[tex]B^2=4 -2[/tex]

Subtract

[tex]B^2=2[/tex]

Take square root of both sides:

[tex]B=\sqrt{2}[/tex]

b= 0 because you take the square root of 2 + the square root of 3 and then subtract that by the square root of 2 and then subtract that by the square root of 3 it will give you zero